2020
DOI: 10.1111/acps.13174
|View full text |Cite
|
Sign up to set email alerts
|

Reporting trigger factors for (hypo)manic episodes in bipolar disorder: association with personality and prognosis

Abstract: Smedler E, Sparding T, Hattab A, Sellgren CM, Land en M. Reporting trigger factors for (hypo)manic episodes in bipolar disorder: association with personality and prognosis.Objective: To investigate external factors that trigger manic and hypomanic relapses and how this is associated with personality and clinical outcome measured as number of affective episodes over a 7-year period. Method: This is a prospective cohort study of 204 meticulously characterized Swedish bipolar disorder patients. Personality was ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 36 publications
(36 reference statements)
0
5
0
Order By: Relevance
“…With respect to personality traits, we found that individuals with bipolar disorder scored higher on measures of Neuroticism, Aggressiveness, and Disinhibition compared with controls, but these personality traits were neither associated with worse outcome in bipolar disorder [44], nor with the presence of trigger factors for affective episodes [45].…”
Section: Neuropsychology and Personalitymentioning
confidence: 66%
“…With respect to personality traits, we found that individuals with bipolar disorder scored higher on measures of Neuroticism, Aggressiveness, and Disinhibition compared with controls, but these personality traits were neither associated with worse outcome in bipolar disorder [44], nor with the presence of trigger factors for affective episodes [45].…”
Section: Neuropsychology and Personalitymentioning
confidence: 66%
“…In the meantime, treatment with the usual fi rst-line antidepressant medications may result in the patient "switching" to a manic or hypomanic state. 1 Additionally, because of permanent brain changes that occur in untreated bipolar illness, the longer a person goes without proper treatment, the more irreversible functional defi cits can occur. Th erefore, it is important that the primary care NP screen for BD in patients presenting with symptoms of depression as well as collaborate with and make appropriate referrals to psychiatry so that these patients receive appropriate treatment.…”
Section: E Np Is Puzzled Concerned For the Patient Worried About What...mentioning
confidence: 99%
“…Because patients typically seek treatment for depressive symptoms rather than for elevated and expansive mood, it often takes many years for BD to be properly diagnosed, which puts patients at higher risk for attempted or completed suicide. In the meantime, treatment with the usual first-line antidepressant medications may result in the patient “switching” to a manic or hypomanic state 1. Additionally, because of permanent brain changes that occur in untreated bipolar illness, the longer a person goes without proper treatment, the more irreversible functional deficits can occur.…”
mentioning
confidence: 99%
“…In this severe mood disorder, manic or depressed episode leads to disability of the individual and social functioning of the patient (Rosa et al., 2010 ). Aggression, disinhibited behaviors and disturbed sleep, are some of the symptoms of manic episodes of this disorder (Smedler et al., 2020 ). Despite some differences in the results of some studies, the lifetime prevalence of this disorder estimates 3.3% and its 12‐month prevalence as equal to 2% (Sadocket al., 2017 ).In some studies, the prevalence rate of unipolar mania among patients with bipolar disorder has been reported to be 5% to 7.2% (Baek et al., 2014 ).…”
Section: Introductionmentioning
confidence: 99%